Description of the Characteristics of Nutritional Status Based on Food Intake in School-Age Children - Titih Huriah; Ika Fauziyah Rahmawati (Universitas Muhammadiyah Yogyakarta, 2019)
Background: One of the factors that influence nutritional status is food intake. Imbalance of food intake in school-age children causes nutritional problems occurring due to the decline in the immune system. Objective: This study aims to determine the description of the characteristics of nutritional status based on the school-age children's intake of food.Method: This study used a cross-sectional design with a random sample size of 84 students from grade 1 to grade 6 in Sonosewu Bantul Elementary School. The instruments used in the study were school-age, weight scales, and food records. The variable in this study was the description of nutritional status characteristics based on food intake in school-age children. The data analysis used frequency distribution.Result: The results showed that 57 school-age children (67.85%) had a normal nutritional status. Respondents in this study had less carbohydrate intake (n=64; 76,2%), more protein intake (n=47; 56%), less fat intake (n=56; 66,7%), less vitamin intake (n=49; 58,3%), less mineral intake (n=84, 100%). In children with normal nutritional status, the researcher found that 34 (40,5%) had more protein intake.Conclusion: The majority of school-age children in Sonosewu Bantul Elementary School had normal nutritional status with excessive protein intake. However, their nutrient intake in the form of calories, carbohydrates, fats, minerals, and vitamins were less. This fact may have an impact on the growth and development of school-age children.